2012
DOI: 10.1007/jhep04(2012)049
|View full text |Cite
|
Sign up to set email alerts
|

New physics models of direct CP violation in charm decays

Abstract: In view of the recent LHCb measurement of ∆A CP , the difference between the time-integrated CP asymmetries in D → K + K − and D → π + π − decays, we perform a comparative study of the possible impact of New Physics degrees of freedom on the direct CP asymmetries in singly Cabibbo suppressed D meson decays. We systematically discuss scenarios with a minimal set of new degrees of freedom that have renormalizable couplings to the SM particles and that are heavy enough such that their effects on the D meson decay… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 142 publications
1
53
0
Order By: Relevance
“…A viable possibility is to deviate from the generation universality for the color octet couplings to the quark fields, or to modify the original MFV set-up of [29,37]. Thus, the authors of [43] suggested small deviation from the MFV ansatz by allowing flavor changing u ↔ c quark interactions with a neutral color octet scalar. Following ref.…”
Section: Following [5] One Can Write An Effective Hamiltonian For Nonmentioning
confidence: 99%
See 3 more Smart Citations
“…A viable possibility is to deviate from the generation universality for the color octet couplings to the quark fields, or to modify the original MFV set-up of [29,37]. Thus, the authors of [43] suggested small deviation from the MFV ansatz by allowing flavor changing u ↔ c quark interactions with a neutral color octet scalar. Following ref.…”
Section: Following [5] One Can Write An Effective Hamiltonian For Nonmentioning
confidence: 99%
“…where the couplings G(c → u) and X d are proportional to quark masses: was found that two operatorsÕ 1 S1 = (ūP R s)(sP R c) andÕ 1 S2 = (ū α P R s β )(s β P R c α ) contribute to the effective Hamiltonian as described in [43]. Motivated by the model of [43], we use this tree level effective (c u Φ 8 ) coupling bounded by the charm CP asymmetry.…”
Section: Following [5] One Can Write An Effective Hamiltonian For Nonmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of the effect of NP models that may contribute to the difference CP asymmetry has been performed in Ref. [38]. It points out that the CP violation may be generated at the tree level with models that involve flavor-changing couplings of Z, Z ′ bosons, new charged gauge bosons, flavor-changing heavy gluon, scalar octets, a scalar diquark, or a two-Higgs doublet with minimal flavor violation.…”
Section: Introductionmentioning
confidence: 99%